Control models of data flows in Internet under instability - Ignatenko, O.P. (PROBLEMS IN PROGRAMMING, 2025)
This paper deals with the control model of network data flows. We proposed an approach to analyzing network work using fluid models and conflict control theory domain. We obtained analytic solution for certain class of networks and proved time optimality. We considered special case of network activity – denial of service attack.Prombles in programming 2011; 3: 38-51